2016
DOI: 10.1007/s00228-016-2140-z
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 rs3761548 polymorphism is associated with tacrolimus-induced acute nephrotoxicity in renal transplant patients

Abstract: Our study demonstrated the TAC-induced acute nephrotoxicity was associated with FOXP3 rs3761548 polymorphism in renal transplant patients. FOXP3 rs3761548 might serve as a biomarker to prevent TAC toxicity and help progression toward individualized therapy of TAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…In the present study, female patients with the rs2232365 AA and the rs3761548 AA genotypes had a 1.16‐ and a 1.36‐fold persistent HBV risk than non‐carriers in a recessive model, although this was not significant ( p = 0.68 and 0.38, respectively). There are some studies that revealed no association between these polymorphisms and different diseases in terms of gender groups . These results are consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, female patients with the rs2232365 AA and the rs3761548 AA genotypes had a 1.16‐ and a 1.36‐fold persistent HBV risk than non‐carriers in a recessive model, although this was not significant ( p = 0.68 and 0.38, respectively). There are some studies that revealed no association between these polymorphisms and different diseases in terms of gender groups . These results are consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, patients carrying the rs3761548 AA genotype had a 1.24‐fold higher HBV risk in the co‐dominant model, although this also was not significant ( p = 0.34, OR = 1.24; 95% CI = 0.81–1.86). In the literature, the AA genotype has been indicated to be a risk factor in a few studies . On the other hand, some studies showed an inverse association between different diseases and the rs376148 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently not known whether these effects are related to calcineurin‐dependent mechanisms, but the similarities between cyclosporin and tacrolimus, which have a completely different molecular structure and intracellular binding site, but a similar nephrotoxicity profile, suggest that this may be the case. Current data show that the tacrolimus‐induced acute nephrotoxicity in renal transplant patients may be associated with the FOXP3 rs3761548 variant . In this study, authors concluded that patients with FOXP3 rs3761548 A allele carriers are more likely to experience tacrolimus‐induced acute nephrotoxicity.…”
Section: Introductionmentioning
confidence: 65%
“…FOXP3 polymorphisms may be related to the outcomes of kidney transplantation and previous studies have shown that tacrolimus can target Tregs and inhibit them dose‐dependently and significantly . Previous studies have demonstrated, in KTRs, that the level of CD4+CD25+FOXP3+Tregs was lower in rejection groups compared to stable patients; meanwhile, the number of Tregs was positively correlated with the estimated glomerular filtration rate . Thus, these observations can be explained, at least partially, by an interaction between the FOXP3 rs3761548 variant and tacrolimus nephrotoxicity.…”
Section: Introductionmentioning
confidence: 96%
“…A previous study also did not find association of both FOXP3 variant with acute or chronic rejection, even in a 10-years follow-up period ( Park et al, 2017 ). On the other hand, other studies reported association of the FOXP3 c.-23+2882A>C (A allele) polymorphism with long-term (2 and 5 years) acute rejection or nephrotoxicity in kidney recipients from different populations treated with cyclosporine- or TAC- based immunosuppressive therapy ( Qiu et al, 2012 ; Misra et al, 2016 ; Wu et al, 2017 ). The c.-23+2882A allele was also associated with worst graft survival and higher rate of recurrence of the original glomerular disease in kidney recipients at 3-year post-transplant ( Adamek et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%